Structure Characteristics of Si/Si-Mo Ductile Irons Solidified on a Metallic Chill - I. Stan; D.E. Anca; M. Chisamera; I. Riposan; S. Stan (Archives of Foundry Engineering, 2025)
The present work focuses on the structure characteristics of three un-inoculated ductile cast irons (0.035-0.045%Mgres), at high content of Si and Mo (I. 4.55%Si/4.71%CE; II. 5.25%Si/5.05%CE; III. 4.80%Si-2.30%Mo/4.75%CE) solidified on a cast iron chill, in furan resin sand moulds. At 4.55%Si iron, there resulted a chilled zone at 6-8mm, with carbides presence, lower graphite amount, higher nodule count and ferrite amount. Si increasing up to 5.25%Si led to a limited affected surface zone (up to 3mm), characterised by no carbides and the highest nodule count. Mo addition led to the most extensive chilled zone (11-15mm), with the lowest amount of graphite and ferrite, and the highest carbides amount, at the lowest nodule count. All irons are characterised by Type V, slightly irregular spheroidal graphite morphology, typical for the Roundness Shape Factor RSF=0.62-0.75 range, at the highest position for I, intermediary for II and at the lowest position for III cast irons. A higher Graphite Nodularity (NG) level resulted when it was calculated according to ISO 16112:2017 [CGI], comparing to ISO 945-4-2019 [DI]. By the use of the Sphericity Shape Factor (with graphite real perimeter), an intermediary position of NG was obtained; it is recommended to avoid the castings rejection, due to the lower values of NG resulted from ISO 945-4-2019 stipulation for High-Si DI. The increase of Si negatively affected the nodularity, while the supplementary Mo alloying led to the lowest NG. The chill solidification appears to have less effect on the NG of 4.55%Si iron, with the maximum influence for 4.8%Si-2.3%Mo iron and by the imposed RSF=min.0.80, especially for 5.25%Si content.